Kompetensi Kepribadian Guru Berdasakan 2 Timotius 3: 10-17 - Kurniawan, Fery; Ricard, Ricard; Napriadi, Napriadi; Widyawati, Ni Kadek Sri; Sagala, Lenda Debora J. F. (Jurnal Kala Nea, 2021)
The personality of the teacher is an important factor, whether students get success or failure for the future of educating those who are still in elementary school and for those in the middle class when experiencing mental turmoil. The presentation in this study aims to find and explain the personality competencies that teachers need to have based on 2 Timothy 3:7-10. In this research study using literature study research on biblical texts in 2 Timothy 3: 10-17 which contains the principle of discipleship from Paul to Timothy in an approach using the method of description analysis on the text of 2 Timothy 3: 10-17. So that the characteristics of the personality of Christian Religious Education teachers are obtained. The results found are that the personality of Christian Religious Education teachers is the personality of teachers who are willing to sacrifice, obedient, and diligent so that these personalities can indirectly influence and foster students who are taught and educated by the teacher concerned.